1992
DOI: 10.1210/jcem.75.5.1430093
|View full text |Cite
|
Sign up to set email alerts
|

Clinically nonfunctioning pituitary adenoma and octreotide response to long term high dose treatment, and studies in vitro.

Abstract: We have studied seven patients with a clinically nonfunctioning or alpha-subunit-secreting pituitary macroadenoma, four of whom received long term, high dose octreotide treatment. We have attempted to correlate the presence of somatostatin receptors (SS-R) in the adenomas and the outcome of octreotide treatment, as measured by tumor size, improvements in visual field defects, and hormonal response. The presence of SS-R in the pituitary adenomas was demonstrated in vivo using [111indium]octreotide scintigraphy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 18 publications
3
25
0
3
Order By: Relevance
“…In three previous series, 29 gonadotroph adenomas were studied in cell culture (4,16,17). Somatostatin produced, in vitro, a partial (28±34%) inhibition of FSH, LH or a-subunit in less than 28% of these tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three previous series, 29 gonadotroph adenomas were studied in cell culture (4,16,17). Somatostatin produced, in vitro, a partial (28±34%) inhibition of FSH, LH or a-subunit in less than 28% of these tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such findings led to the study of the effect of long-term octreotide therapy in patients with pituitary tumours which released luteinizing (LH) and follicle-stimulating (FSH) hormones and/or free a-subunit. If octreotide was poorly effective upon tumour shrinkage, a significant reduction in serum FSH concentrations could be found in two out of four patients under long-term octreotide administration (4). More recently, it was shown by cell culture studies that somatostatin and its analogue, lanreotide, inhibited the proliferation of dispersed human non-functioning pituitary cells (5), which, in their majority, do synthesize LH, FSH or the a subunit (6±8).…”
Section: Introductionmentioning
confidence: 99%
“…45 Therapy with octreotide seldom results in a reduction in the size of the tumor, but 30 to 40 percent of patients have improvement in visual-field defects within days after the initiation of treatment. 46 This response may reflect a direct effect of octreotide on the retina or optic nerve.…”
Section: Nonsecretory Pituitary Adenomasmentioning
confidence: 99%
“…Katznelson et al (6) reported that octreotide reduced tumor size with or without an accompanyingdecrease in serum tumor marker levels in a small percentage of patients with clinically nonfunctioning pituitary tumors and oc-subunit hypersecretion. De Bruin et al (35) reported that high-dose, 1,200 jug/day, octreotide treatment induced improvement of visual field defects in three of four patients with clinically nonfunctioning pituitary adenomaand the effect of a single injection of octreotide on the gonadotropin levels had no correlation with the improvement of the clinical efficacy. Holland et al (36) reported that, from the results of the relation of the expression of five somatostatin receptor subtypes with the effect of somatostatin and its analogs on the secretion of gonadotropin from gonadotropinomacells in culture, novel somatostatin receptor subtype specific somatostatin analogs might be of benefit in the treatment of selected patients with somatostatin receptor positive secreting tumors not responding to octapeptide somatostatin-analog.…”
Section: Discussionmentioning
confidence: 99%